TEORI DALAM PENGAJARAN SASTRA - I Wayan Artika (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2015)
This article studies about the monotonous of literary teaching which is not the only problem, but also the student’s low motivation, the shift from conventional text to digital text, and low esteem perspective on literature. Teacher does not have other choices, except to teach theoretically and monotonously as if there is no other choices. The problem in this study is very basic, it is urgent to talk about something basic too, such as literature definition, power and strength of literature and the situation of literature teaching. To help teachers develop the teaching method, the focus of this article is to talk about literature theories which is explained effectively completed by real example of literature teaching.Keywords : literature teaching, literature theory